Le “promesse tecnologiche” della blockchain nell’industria musicale digitale (De Musica, 2021)
The article analyzes the emergence of blockchain technology in music industry, unfolding narratives, expectations and promises surrounding blockchain’s impact on the circulation of digital music. Blockchain is increasingly addressed as the upcoming “revolution” in music industry and is often acclaimed as a new “disruptive technology”, able to change the game in the music business. The article analyzes how this innovation is discursively constructed by news articles, start-ups, self-presentations, and other documents. From a theoretical point of view, the analysis relies on concepts coming from Science & Technology Studies (STS), information infrastructure studies and the study of technological promises, thus enriching the intersection between sound studies and STS. On these bases, the article outlines an overview of the ‘hype’ discourse generated around music blockchain, recognizing five main technological promises supporting the adoption of blockchain. Moreover, it also brings to the foreground some concerns about the possible consequences of this adoption for the evolution of music value and music circulation processes.
Keywords: Blockchain; digital music; music industry; infrastructures; technological promises